Application of Health Belief Model on Obesity Prevention Behavior in Adolescents - Viola Holly Flora; Eti Poncorini Pamungkasari; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Adolescent obesity is a global challenge with serious health impacts. This study aimed to explore the application of the Health Belief Model (HBM) in the context of preventing obesity in adolescents. Subjects and Method: This research uses an observational analytical design with a cross sectional approach. The population consists of teenagers aged 15-19 years in the city of Surakarta, with a sample of 200 teenagers chosen randomly. The dependent variable is obesity prevention behavior. The independent variable is the HBM construct (perceived vulnerability, perceived seriousness, perceived benefits, perceived barriers, cues to action, and self-efficacy). Data was collected using a questionnaire, and analyzed using multiple linear regression. Results: There is a positive and statistically significant relationship between perceived vulnerability (b= 0.08; 95% CI= 0.03 to 0.13; p = 0.004), perceived seriousness (b= 0.37; 95% CI= 0.29 to 0.46; p<0.001), perceived benefits (b= 0.22; 95% CI= 0.14 to 0.29; p<0.001), cues to action (b= 0.15; 95% CI= 0.05 to 0.25; p= 0.005) and self-efficacy (b= 0.05; 95% CI = 0.01 to 0.10; p= 0.027) on obesity prevention behavior. Adjusted R-squared= 72.15%. This means that the HBM construct includes perceptions of vulnerability, perceptions of severity, perceptions of benefits, cues to action, and self-efficacy, together they are able to explain variations in obesity preventive behavior in adolescents by 72.15%. Conclusion: The results of this study indicate that the Health Belief Model construct includes perceptions of vulnerability, perceptions of seriousness, perceptions of benefits, cues to action, and self-efficacy, which play a role together in shaping obesity prevention behavior in adolescents.